Cost and outcome of occupation-based practice for community dwelling frail elderly: a pilot study - Nagayama H (Dove Medical Press, 2018)
Hirofumi Nagayama,1 Norikazu Kobayashi,2 Yu Ishibashi,2 Ryuji Kobayashi,2 Chika Murai,3 Keita Yamauchi4 1Department of Occupational Therapy, Kanagawa University of Human Services, Yokosuka, Japan; 2Division of Occupational Therapy, Faculty of Health Sciences, Tokyo Metropolitan University, Arakawa, Japan; 3Department of Occupational Therapy, Ishikawa Prefectural Takamatsu Hospital, Kahoku, Japan; 4Graduate School of Health Management, Keio University, Fujisawa, Japan Purpose: The purpose of this pilot study was to determine the effectiveness and costs of the occupation-based practice for community dwelling frail elderly. Design: Pilot pre-post design without a control group. Setting: A care management center involving 37 local elderly. Subject: The final analysis included 26 frail elderly in a community dwelling center. Intervention: The intervention was occupation-based practice involving setting of client-centered goals, observation of real living situations, and provision of advice on the individual problem of real occupation. Outcome: The outcome was the Frenchay Activities Index (FAI), which is used to evaluate the instrumental activities of daily living (IADL). Additionally, the frequency, duration, and cost of the intervention were calculated. Results: Regarding the FAI score before and after the interventions, there were significant improvements in all items except work (P<0.05, effect size [r]: 0.67–0.93). A total of 15 people out of 26 (57.7%) showed improvement in activities of daily living. The frequency of interventions was 3.7 (95% confidence interval [CI]: 2.83–4.48), and the duration was 7.4 weeks (95% CI: 5.27–9.42). The average intervention cost was $258 (95% CI: 200.4–317.4). Conclusion: The results of this study showed that occupation-based practice has a potential to improve IADL in frail elderly, with low frequency of intervention, within a short-term, and direct cost reduction. We believe that this pilot study will contribute to future clinical studies for frail elderly, and the findings can be easily applied to daily clinical intervention. A well-designed prospective randomized-controlled trial is necessary to verify these results. Keywords: activities of daily living, Frenchay Activities Index, frail elderly, occupational therapy, cost saving